أسلوبا الترجمة بالاقتباس والتنوع في الترجمة النصية لفيلم "أليفيا 2053" - Habibullah, Romadhoni; Supriadi, Dedi; Firdaus, Rifqi Muhammad; Wahab, Wahab (Lughaat: Journal of Arabic Linguistics, 2026)
This study discusses the application of adaptation and variation techniques in the subtitles of Alephia 2053, an Arabic-language animated film with a dystopian theme that is rich in social and political criticism. The main focus of this study is how translators convey the meaning of the source language dialogue into Indonesian while considering cultural context, emotional expression, and the dramatic and communicative effectiveness of the message. This study applies a qualitative descriptive method, using Molina and Albir’s classification of translation techniques as an analytical framework to examine specific instances of subtitle translation in the film. Data was collected from the official subtitles of the film and analyzed to examine the forms and functions of the use of adaptation and variation techniques. The results of the study indicate that adaptation techniques are widely used to align meaning with the cultural context of Indonesia, particularly in idiomatic and emotionally charged expressions. In expressions with idiomatic and emotional content. Meanwhile, variation techniques appear in the form of changes in sentence structure, additional emotional intensity, and alignment of speaking style to feel natural in the target language. Both techniques have proven effective in reviving the narrative message of the film without sacrificing meaning accuracy. This study that success in audiovisual translation is largely determined by the translator's ability to understand linguistic and cultural nuances, as well as their sensitivity to the accompanying visual and audio dynamics.